Production and Characterization of Polyhydroxyalkanoates and Native Microorganisms Synthesized from Fatty Waste - Javier Ricardo Gómez Cardozo; Amanda Lucía Mora Martínez; María Yepes Pérez; Guillermo Antonio Correa Londoño (International Journal of Polymer Science)
Polyhydroxyalkanoates (PHAs) are biodegradable and biocompatible plastics. They are synthesized by a wide variety of microorganisms (i.e., fungi and bacteria) and some organisms such as plants, which share characteristics with petrochemical-based plastics. The most recent studies focus on finding inexpensive substrates and extraction strategies that allow reducing product costs, thus moving into a widespread market, the market for petroleum-based plastics. In this study, the production of polyhydroxybutyrate (PHB) was evaluated using the native strains, Bacillus megaterium, Bacillus sp., and Lactococcus lactis, and glycerol reagent grade (GRG), residual glycerol (RGSB) byproduct of biodiesel from palm oil, Jatropha oil, castor oil, waste frying oils, and whey as substrates. Different bacteria-substrate systems were evaluated thrice on a laboratory scale under different conditions of temperature, pH, and substrate concentration, employing 50 mL of broth in 250 mL. The bacterial growth was tested in all systems; however, the B. megaterium GRG system generated the highest accumulation of PHA. The previous approach was allowed to propose a statistical design optimization with RGSB (i.e., RGSB, 15 g/L, pH 7.0, and 25°C). This system reached 2.80 g/L of PHB yield and was the optimal condition tested; however, the optimal biomass 5.42 g/L occurs at pH 9.0 and 25°C, with a substrate concentration of 22 g/L.